Development of Game on Mobile Application to enhance Critical Thinking Skills for Secondary Students - Meesanga, Jiraporn; Kaosamlee, Chanakarn; Saenboonsong, Siripon (Ratchaphruek Journal, 2025)
This research was research and development. The purpose of this research was to develop a game on a mobile application to enhance critical thinking of secondary students. The group of informants consists of 25 people, including administrators, teachers, and experts, selected through purposive selection. The target group for the trial use of the developed game on the mobile application was conducted with 35 secondary students under the secondary educational service area office of Phranakhon Si Ayutthaya, selected through purposive sampling. The research tools were the game on the mobile application to enhance critical thinking, the interview form, and the effectiveness assessment form for the game on the mobile application. The statistics used in the research include the content analysis, mean, and standard deviation. The results showed that the development of games on mobile applications to enhance critical thinking for secondary students followed the 7-step System Development Life Cycle (SDLC) model. The results of the development of the games on the mobile application can be used on both Android smartphones and web browsers. There was a registration system. There were quiz games designed to enhance critical thinking through animated cartoon situations, featuring beautiful color and sound commentary with musical accompaniment. The system reports and collects scores. The results of the evaluation of the effectiveness of the game on the mobile application by the expert were at a high level.